2020
DOI: 10.1007/s11657-020-0698-7
|View full text |Cite
|
Sign up to set email alerts
|

‘Nonagenarians’ with a hip fracture: is a different orthogeriatric treatment strategy necessary?

Abstract: Nonagenarians differ from patients aged 70-79 and 80-89 years in baseline characteristics, complication and mortality rates. Differences increased gradually with age. The results of this study can be used, in combination with the Almelo Hip Fracture Score, to deliver efficiently targeted orthogeriatric treatment to the right patient group. Purpose In previous literature, elderly with a hip fracture are frequently defined as ≥ 70 years. However, given the ageing population and the rapidly increasing number of '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
2
9
0
1
Order By: Relevance
“…A better prediction might be possible in a study population with higher mortality rates. De Groot et al (2020) showed that the oldest hip fracture patients (i.e., 90 years and older, the so-called nonagenarians) have a significantly higher 30-day mortality rate of 13.3% compared to their younger peers (4.3% and 8.5% in patients aged 70–79 years and 80–89 years, respectively) [ 15 ]. Developing a risk score in patients 90 or older could improve the prediction.…”
Section: Introductionmentioning
confidence: 99%
“…A better prediction might be possible in a study population with higher mortality rates. De Groot et al (2020) showed that the oldest hip fracture patients (i.e., 90 years and older, the so-called nonagenarians) have a significantly higher 30-day mortality rate of 13.3% compared to their younger peers (4.3% and 8.5% in patients aged 70–79 years and 80–89 years, respectively) [ 15 ]. Developing a risk score in patients 90 or older could improve the prediction.…”
Section: Introductionmentioning
confidence: 99%
“…There have been different reports of bad prognostic factors (female gender, osteoporosis, higher age, complex fracture patterns) when choosing an operative treatment ( 13 , 14 ). But due to the fact that in the elderly and nonagenarian population comorbidities, resiliencies and lifestyles differ immensely and the life expectation is not calculatable; all authors concluded that an individual decision-making is most important ( 7 , 53 ).…”
Section: Considerations and Conclusionmentioning
confidence: 99%
“…Publikované sú informácie o včasnej letalite seniorov s konkrétnym ochorením -napr. infarktom myokardu (2-4), chlopňovými chybami (5-6), srdcovým zlyhaním (7-8), redukovanou funkciou obličiek (9)(10)(11)(12), cievnou mozgovou príhodou (13)(14)(15), infekciami (16)(17), zlomeninou (18)(19)(20), neopláziami (21)(22)(23)(24)(25), delíriom (26), pričom sú často viazané na konkrétny druh vykonanej liečby. Hodnotenie M24 je pritom publikované zriedkavejšie ako pri dlhších časových intervaloch, a to aj pri akútnych chorobách.…”
Section: Diskusiaunclassified